Qualitative Analysis of the Role of Basketball Intern Students in Developing Early-Age Athletes’ Skills - Miranda Aulia Agustin; Dwi Setya Arianza Nuzzaman; Febi Kanaya Sani; Muhammad Iqba Feriantoro (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: Early childhood skill development through sports, particularly basketball, is essential for fostering motor abilities, discipline, and social interaction. Internship programs provide students with opportunities to connect theory with practice while contributing to children’s growth. This study aims to explore the role of internship students in developing early childhood skills through basketball training. Methods: A qualitative approach was employed, using interviews, observations, and documentation. The study involved five internship students who participated in basketball training sessions with young children. Result: The findings revealed that internship students performed multiple roles as coaches, educators, facilitators, and motivators. Play-based strategies such as mini games, paired exercises, and light challenges were effective in maintaining children’s engagement. Basketball training contributed positively to children’s motor skills, discipline, self-confidence, and social interaction. Key challenges included limited facilities, children’s short attention spans, and environmental constraints, which were addressed through creative instructional adaptations. Conclusion: The study highlights the importance of creativity in coaching and demonstrates how internship students contribute to early childhood skill development. It supports motor learning theory and experiential learning concepts, emphasizing the value of practical, play-based approaches in sports education.